Diplomacy - Kissinger, Henry 1923- (Simon & Schuster, 1994)
The seminal work on foreign policy and the art of diplomacy. Moving from a sweeping overview of history to blow-by-blow accounts of his negotiations with world leaders, Henry Kissinger describes how the art of diplomacy has created the world in which we live, and how America's approach to foreign affairs has always differed vastly from that of other nations. Brilliant, controversial, and profoundly incisive, Diplomacy stands as the culmination of a lifetime of diplomatic service and scholarship. It is vital reading for anyone concerned with the forces that have shaped our world today and will impact upon it tomorrow.